Feeding competition within a feral goat population on the Isle of Rum, NW Scotland - Shi, J; Dunbar, R (2006)
This study investigated feeding competition within and between different age-sex classes of feral goats (Capra hircus) on the Isle of Rum (northwest Scotland) from August to November 2000 (inclusive). Although contests in a feeding context were common, most were relatively passive: little overt agonistic behaviour was observed between opponents and the distance between feeding animals involved did not change significantly after an interaction. Month (but not sex or habitat type) had a significant effect on feeding interaction rates, and the proportion of interactions involving more intense forms of conflict was highest in November when forage availability was beginning to decline. The results show that the initiator won most feeding encounters, with adult males being dominant over females. The ability to win conflicts increased with age for both males and females. However, it decreased sharply for adult males older than 5 years, which may, in part, explain the reduced overwinter survival of these individuals. © Japan Ethological Society and Springer-Verlag 2005.